2021
DOI: 10.3389/fneur.2021.662855
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neurite Orientation Dispersion and Density Imaging and Two-Compartment Spherical Mean Technique Parameter Maps in Multiple Sclerosis

Abstract: Background: Neurite orientation dispersion and density imaging (NODDI) and the spherical mean technique (SMT) are diffusion MRI methods providing metrics with sensitivity to similar characteristics of white matter microstructure. There has been limited comparison of changes in NODDI and SMT parameters due to multiple sclerosis (MS) pathology in clinical settings.Purpose: To compare group-wise differences between healthy controls and MS patients in NODDI and SMT metrics, investigating associations with disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 45 publications
(72 reference statements)
2
22
0
Order By: Relevance
“…39 Abnormality 4 also has lower v cyl and λ cyl than average WM and exemplifies typical white matter lesions in multiple sclerosis reported in Ref. 40. We highlight that these abnormalities are not exact representations of specific pathologies, which vary widely, but serve to demonstrate estimation performance in abnormal tissue configurations likely to arise in practice.…”
Section: Simulated Abnormal Parameter Combinationssupporting
confidence: 58%
“…39 Abnormality 4 also has lower v cyl and λ cyl than average WM and exemplifies typical white matter lesions in multiple sclerosis reported in Ref. 40. We highlight that these abnormalities are not exact representations of specific pathologies, which vary widely, but serve to demonstrate estimation performance in abnormal tissue configurations likely to arise in practice.…”
Section: Simulated Abnormal Parameter Combinationssupporting
confidence: 58%
“…Somewhat surprisingly, given a weak negative association reported elsewhere, 60 NODDI ICVF and ISOVF were weakly positively related at low ISOVF values. A larger ‘hindered’ diffusion volume fraction (ECVF), assumed to be due to glial cells infiltration and cell bodies, could lead to both a reduction in ISOVF and ICVF.…”
Section: Discussionmentioning
confidence: 53%
“…In our cohort of patients with recently diagnosed RRMS, we observed an unexpected increase in NODDI ICVF within NAWM over one year. NODDI ICVF represents the 'restricted' diffusion signal fraction within the non-isotropic diffusion signal; ICVF is typically lower in RRMS compared to healthy controls 28,60,67 and longitudinal decreases in NAWM ICVF have previously been noted. 68 The biological mechanism driving the increase in NODDI ICVF, with no concomitant change in ISOVF, is unclear, but could partly be attributed to axonal swelling, axonal bundling following demyelination, or axonal repair.…”
Section: Normal-appearing White Mattermentioning
confidence: 99%
“…Several studies have reported that DTI is superior to conventional MRI in the evaluation of NAWM in MS patients; however, advanced dMRI techniques, as described in this review, are more sensitive and have the potential to show specific pathological changes in the microstructure in vivo . Clinically, advanced dMRI has been reported to be more sensitive in detecting microstructural changes in the brain that correlate with patient disability 118 and in tracking disease progression in NAWM over time, even before clinical symptoms occur. 119 In addition, several reports have shown the usefulness of advanced dMRI in NAWM and demyelinating foci.…”
Section: Discussionmentioning
confidence: 99%